An Unusual Acute Otitis Media Complication: Luc’s Abscess - Meltem Akpınar; Beyza Demirci (Turkish Archives of Otorhinolaryngology)
Otitis media, a common childhood disease, can lead to serious complications such as acute mastoiditis and, rarely, Luc’s abscess, with life-threatening consequences. Luc’s abscess, a rare but severe complication, can occur without acute mastoiditis. This case report details a case of Luc’s abscess in a 14-year-old girl with acute otitis media, presenting with ear pain, facial swelling, and hearing loss. Treatment involves a multidisciplinary approach, considering factors like age and abscess extent. Though there is no established standard treatment, this case emphasizes the need for prompt recognition and appropriate intervention to prevent severe complications. This case report emphasizes the importance of tailored, timely interventions for optimal outcomes in affected children.